Primer registro de Abrothrix jelskii (Thomas 1824) para Chile - Valladares Faúndez, Pablo; Álvarez Henríquez, Nicole; Urrutia, Natalia; Nassar San Martín, Carlos; Iriarte, Agustín (Gayana, 2015)
Sin resumen